INTELLECTUAL INFLUENCE CAPITAL ON PERFORMANCE FINANCE WITH STRATEGY BUSINESS AS MODERATION (Empirical Study of Companies Food Sector Manufacturing And Drinks Listed on the IDX Year 2019 – 2021) - Stefania Lewa Lam; Antoni Antoni (WORLDVIEW ( Development economic and sharia studies journal ), 2024)
The aim of this research is to identify the impact of intellectual capital on financialperformance by considering business strategy as a moderating factor. In this research, the populationused is manufacturing companies operating in the food and beverage sector listed on the IndonesiaStock Exchange from 2019-2021. For sampling, this research used a purposive sampling technique,where 16 food and drink samples were selected that met predetermined criteria. This research usesSPSS 21. In this research, moderated regression analysis is used. The results of data analysis show thatintellectual capital does not have a direct significant influence on financial performance, but theinfluence of intellectual capital on financial performance can be moderated with the help of businessstrategy. Therefore, companies must identify intellectual resources and build a moderate businessstrategy